Theorizing European integration - Chryssochoou, Dimitris N., 1970- (London : SAGE, 2001)
This work provides a comprehensive introduction to theories of European integration in the contemporary study of Europe, the European Union and European integration.
Cover -- Summary of Contents -- Contents -- List of Abbreviations -- Acknowledgements -- Introduction -- Part I: Theory -- Chapter 1 -- Integration Theory and its Uses -- Part II: Theories -- Chapter 2 -- Formative Theories: Structure v. Process -- Chapter 3 -- The Consensual Phase: Autonomy through Control -- Part III: Theorizing -- Chapter 4 -- Paradgim Shift: From Policy to Policy -- Chapter 5 -- Theorizing the European Consociation -- Part IV: Metatheory -- Chapter 6 -- Capturing the Normative Turn -- Bibliography.
Includes bibliographical references (pages 199-216) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: European Union; European Union; European federation; Europe -- Politics and government -- 1989-; Construction européenne.; Europe -- Politique et gouvernement -- 1989-; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; European federation; Politics and government; Europe; Europese integratie; Theorieën.; Since 1989; Libros electrónicos.